2009
DOI: 10.1037/a0016230
|View full text |Cite
|
Sign up to set email alerts
|

It takes two to tango: How parents’ and adolescents’ personalities link to the quality of their mutual relationship.

Abstract: According to J. Belsky's (1984) process model of parenting, both adolescents' and parents' personality should exert a significant impact on the quality of their mutual relationship. Using multi-informant, symmetric data on the Big Five personality traits and the relationship quality of mothers, fathers, and two adolescent children, the current study set out to test this prediction. Adolescents' agreeableness and parents' extraversion emerged as predictors of relationship warmth, whereas parents' openness emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 65 publications
7
65
2
1
Order By: Relevance
“…In sum, the pattern of findings from this study provide further evidence for the distinction between positive and negative relationship attributes such as conflict and warmth (e.g., Denissen et al., 2009; Pianta, 1999). Developmental patterns of mother–son conflict were linked to the temperamental characteristics of the son during early childhood and deviancy training (i.e., antisocial behavior) during adolescence.…”
Section: Discussionsupporting
confidence: 63%
“…In sum, the pattern of findings from this study provide further evidence for the distinction between positive and negative relationship attributes such as conflict and warmth (e.g., Denissen et al., 2009; Pianta, 1999). Developmental patterns of mother–son conflict were linked to the temperamental characteristics of the son during early childhood and deviancy training (i.e., antisocial behavior) during adolescence.…”
Section: Discussionsupporting
confidence: 63%
“…In this way, CRB appeals to children's ability to distance themselves from the here-and-now and to solve problems on their own. In Denissen et al (2009), no main effect of child age was, however, reported on parental warmth and control towards 12-and 14-year-old adolescents. Second, in this study we also consider the parental and child predictors as timevarying or as time-invariant predictors according to their conceptual properties (Hoffman & Stawski, 2009).…”
Section: Current Studycontrasting
confidence: 53%
“…For example, parents may struggle to provide support or find it difficult to maintain positive relationships with highly reactive, dysregulated sons, which may impede subsequent improvements in children’s regulatory abilities. It seems possible that parent–child relationship quality may have particular importance during adolescence than in childhood because teens are better able to make meaningful contributions to the parent–child relationship (Denissen et al 2009). The notion that adolescents are able to contribute to their own self-regulatory socialization warrants further attention, and is a necessary step in future evaluations of the theoretical model underlying this investigation.…”
Section: Discussionmentioning
confidence: 99%